Adalimumab in acute sciatica reduces the long-term need for surgery: a 3-year follow-up of a randomised double-blind placebo-controlled trial. Issue 4 (13th October 2011) - Genevay, S; Finckh, A; Zufferey, P; Viatte, S; Balagué, F; Gabay, C
Abstract : Introduction: Two subcutaneous injections of adalimumab in severe acute sciatica significantly reduced the number of back operations in a short-term randomised controlled clinical trial. Objective: To determine in a 3-year follow-up study whether the short-term benefit of adalimumab in sciatica is sustained over a longer period of time. Methods: The primary outcome of this analysis was incident discectomy. Three years after randomisation, information on surgery could be retrieved in 56/61 patients (92%).A multivariate Cox proportional hazard models, adjusted for potential confounders, was used to determine factors predisposing to surgery. Results: Twenty-three (41%) patients had back surgery within 3 years, 8/29 (28%) in the adalimumab group and 15/27 (56%) in the placebo group, p=0.04. Adalimumab injections reduced the need for back surgery by 61% (HR)=0.39 (95% CI 0.17 to 0.92). In a multivariate model, treatment with a tumour necrosis factor-α antagonist remained the strongest protective factor (HR=0.17, p=0.002). Other significant predictors of surgery were a good correlation between symptoms and MRI findings (HR=11.6, p=0.04), baseline intensity of leg pain (HR=1.3, p=0.06), intensity of back pain (HR=1.4, p=0.03) and duration of sickness leave (HR=1.01 per day, p=0.03). Conclusion: A short course of adalimumab in patients with severe acute sciatica significantly reduces the need for back surgery.